2002
DOI: 10.1161/hs0302.104111
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Brain Damage in Stroke-Prone Rats

Abstract: Background and Purpose-The spontaneously hypertensive stroke-prone rat (SHRSP) is an animal model for a complex form of cerebrovascular pathology. MRI provides an efficient and noninvasive tool for studying the time course of brain damage. The aim of this study was to gain new insights into the pathological phenomena responsible for the occurrence of brain injury in SHRSP with the use of the apparent diffusion coefficient of water (ADC), one of the most efficient MRI parameters for detecting brain abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 37 publications
5
77
2
Order By: Relevance
“…The cumulative appearance of microinfarcts in one brain region can induce expanded tissue necrosis ( Figure 5A) otherwise typical for occlusions of bigger brain vessels (macroangiopathy) or cerebral lesions of SHRSP fed a salt loaded diet with 1% NaCl added to their drinking water (Guerrini et al, 2002). The development of (vasogenic) edema illustrated by T2 sequences in MRI ( Figures 5A and 5D) further decreases CBF ( Figure 6B).…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative appearance of microinfarcts in one brain region can induce expanded tissue necrosis ( Figure 5A) otherwise typical for occlusions of bigger brain vessels (macroangiopathy) or cerebral lesions of SHRSP fed a salt loaded diet with 1% NaCl added to their drinking water (Guerrini et al, 2002). The development of (vasogenic) edema illustrated by T2 sequences in MRI ( Figures 5A and 5D) further decreases CBF ( Figure 6B).…”
Section: Discussionmentioning
confidence: 99%
“…We observed an increase in ADC in the untreated animals that was corrected with minocycline; increased ADC may be seen in vasogenic edema, which was seen as an increase in WM lesions in T2-weighted signal. 7,35 Fractional anisotropy is composed of radial and axial diffusivity. Untreated animals showed reduced FA, which could be explained by an increase in radial diffusivity secondary to loss of WM tissue integrity.…”
Section: Discussionmentioning
confidence: 99%
“…20 weeks. 35 A recent study showed that SHR/SP with JPD and added salt developed increased permeability before development of intracerebral bleeding. 37 We combined the JPD with occlusion of one carotid to accelerate the pathologic changes in the WM; we began the abnormal diet at the twelve rather than the sixth week, resulting WM damage that was generally seen before strokes.…”
Section: Discussionmentioning
confidence: 99%
“…The ischemic volume was determined by trace of apparent diffusion coefficient maps (Tr(D)) computation as previously described (23,24). The progression of the ischemic damage was assessed over time using ANOVA for repeated measurements with lesion volume (evaluated by MRI) as dependent variable and the treatment as independent variable.…”
Section: Mri Evaluationmentioning
confidence: 99%